2015
DOI: 10.1111/oik.02860
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad and the Ulva: the density dependent role of macroalgal subsidies in influencing diversity and trophic structure of an estuarine community

Abstract: Worldwide, ecological subsidies enhance ecosystem productivity and therefore trophic support for greater biodiversity of taxa. While studies in terrestrial and aquatic ecosystems demonstrate that the magnitude of subsidies into ecosystems diff ers widely, the thresholds where subsidies may switch from exerting positive to negative eff ects are poorly understood. In estuaries, eutrophication promotes drift macroalgae that deposit on the benthos, cover intertidal fl ats for months and serve as pressed resource s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 90 publications
(112 reference statements)
0
7
1
Order By: Relevance
“…Subsurface-deposit feeders are less likely to be affected; however, these deeper prey are less important for many short-billed shorebirds that are limited to feeding on shallow, surface-deposit-feeders and epifauna. The impact of A. vermiculophyllum for foraging shorebirds depends on their dietary flexibility, and the magnitude of the changes to the abundance and distribution of the prey community [4,5,31,32]. Observing shorebird distribution and behavior may provide a clearer, more integrated picture of how A. vermiculophyllum affects prey resources than monitoring invertebrates directly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsurface-deposit feeders are less likely to be affected; however, these deeper prey are less important for many short-billed shorebirds that are limited to feeding on shallow, surface-deposit-feeders and epifauna. The impact of A. vermiculophyllum for foraging shorebirds depends on their dietary flexibility, and the magnitude of the changes to the abundance and distribution of the prey community [4,5,31,32]. Observing shorebird distribution and behavior may provide a clearer, more integrated picture of how A. vermiculophyllum affects prey resources than monitoring invertebrates directly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when considering the effects of A. vermiculophyllum on shorebirds, the most important traits to consider would be foraging mode, rather than diet. Macroalgae change the structure of substrate [19], may obscure visual foraging cues [31], and alter prey distributions [4,32]. It is possible shorebirds with specialized foraging modes for soft muds would be unable to optimally forage from the vegetated microhabitat created by A. vermiculophyllum.…”
Section: Introductionmentioning
confidence: 99%
“…In preparation for the 2008 Beijing Olympic sailing events, 1 × 10 6 t were removed from Qingdao in the Yellow Sea at a cost of >US$85 million (Liu, Keesing, Xing, & Shi, ; Smetacek & Zingone, ). The magnitude of the effect of such blooms may vary, however, dependent on functional group (Green, Sutula, & Fong, ), their severity (Green & Fong, ), their timing (Olyarnik & Stachowicz, ) and their persistence (Arroyo & Bonsdorff, ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that DIN additions change algal group diversity and the abundance of different groups, suggesting that ambient DIN concentrations should not exceed breakpoint concentrations (25 and 50 μ mol L −1 ). On the other hand, Green and Fong (2015) focused on the effect of eutrophication on macrofauna and microphytobenthos diversity (community) as well as sediment iron and sulfide concentrations (ecosystem functioning). The authors identified a point beyond which macroalgal mat thickness (used to represent eutrophication) reduced macrofauna biodiversity (> 1.5 cm).…”
Section: Resultsmentioning
confidence: 99%